Regeneration of Humeral Head Using a 3D Bioprinted Anisotropic Scaffold with Dual Modulation of Endochondral Ossification. Issue 12 (8th February 2023) - Li, Tao; Ma, Zhengjiang; Zhang, Yuxin; Yang, Zezheng; Li, Wentao; Lu, Dezhi; Liu, Yihao; Qiang, Lei; Wang, Tianchang; Ren, Ya; Wang, Wenhao; He, Hongtao; et al.
Abstract: Tissue engineering is theoretically thought to be a promising method for the reconstruction of biological joints, and thus, offers a potential treatment alternative for advanced osteoarthritis. However, to date, no significant progress is made in the regeneration of large biological joints. In the current study, a biomimetic scaffold for rabbit humeral head regeneration consisting of heterogeneous porous architecture, various bioinks, and different hard supporting materials in the cartilage and bone regions is designed and fabricated in one step using 3D bioprinting technology. Furthermore, orchestrated dynamic mechanical stimulus combined with different biochemical cues (parathyroid hormone [PTH] and chemical component hydroxyapatite [HA] in the outer and inner region, respectively) are used for dual regulation of endochondral ossification. Specifically, dynamic mechanical stimulus combined with growth factor PTH in the outer region inhibits endochondral ossification and results in cartilage regeneration, whereas dynamic mechanical stimulus combined with HA in the inner region promotes endochondral ossification and results in efficient subchondral bone regeneration. The strategy established in this study with the dual modulation of endochondral ossification for 3D bioprinted anisotropic scaffolds represents a versatile and scalable approach for repairing large joints. Abstract : A 3D bioprinted joint scaffold with anisotropic structures and heterogeneous components is successfully fabricated in one step. Meanwhile, orchestrated biomechanical and biochemical stimuli are applied for the dual modulation of endochondral ossification to regenerate heterogeneous hyaline cartilage and subchondral bone simultaneously. This approach may provide an alternative for the design, fabrication, and regeneration of biomimetic joints.